2015
DOI: 10.1002/jmrs.103
|View full text |Cite
|
Sign up to set email alerts
|

Using the apparent diffusion coefficient to identifying MGMT promoter methylation status early in glioblastoma: importance of analytical method

Abstract: IntroductionAccurate knowledge of O6-methylguanine methyltransferase (MGMT) gene promoter subtype in patients with glioblastoma (GBM) is important for treatment. However, this test is not always available. Pre-operative diffusion MRI (dMRI) can be used to probe tumour biology using the apparent diffusion coefficient (ADC); however, its ability to act as a surrogate to predict MGMT status has shown mixed results. We investigated whether this was due to variations in the method used to analyse ADC.MethodsWe unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
1
29
3
Order By: Relevance
“…Thus when incorporating these factors into the radiomics signature, there was no additional positive effect on the improvement of the prediction performance, but rather an increased complexity of the prediction model. Additionally, even though it was reported that ADC values were correlated with MGMT promoter methylation and prognosis in GBM [22,32,33], our results indicated that radiomic features extracted from T1-CE and T2-FLAIR sequences performed better than those extracted from the ADC sequence. A potential reason for this observation is the relatively poor imaging resolution of ADC, which limited the stability and robustness of the derived radiomics features.…”
Section: Discussioncontrasting
confidence: 74%
“…Thus when incorporating these factors into the radiomics signature, there was no additional positive effect on the improvement of the prediction performance, but rather an increased complexity of the prediction model. Additionally, even though it was reported that ADC values were correlated with MGMT promoter methylation and prognosis in GBM [22,32,33], our results indicated that radiomic features extracted from T1-CE and T2-FLAIR sequences performed better than those extracted from the ADC sequence. A potential reason for this observation is the relatively poor imaging resolution of ADC, which limited the stability and robustness of the derived radiomics features.…”
Section: Discussioncontrasting
confidence: 74%
“…Also, in the latter study no effect on overall survival of MGMT status was seen, contrary to expectations. Rundle-Thiele et al (95) demonstrated that these discrepancies also may be attributed to differences in methodology. In the same patient population, they used both a minimum ADC region of interest and a histogram analysis and found a trend toward higher mean minimum ADC ratio and significantly lower ADC L in methylated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…25 One study was prospective in design. 26 Twenty studies were retrospective, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27,28,[30][31][32] and 1 study did not explicitly state the design. 29 Study enrollment was consecutive in 3 studies 16,18,25 and not explicit in the remaining studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…29 Study enrollment was consecutive in 3 studies 16,18,25 and not explicit in the remaining studies. Fifteen of 22 studies used methylation-specific polymerase chain reaction as a reference standard to detect MGMT methylation, 11,[14][15][16][19][20][21][22][23][24]27,28,[30][31][32] with the other studies using DNA methylation analysis, 18 pyrosequencing, 13 immunohistochemical staining, 29 or multiplex ligation-dependent probe amplification, 26 with the method not being stated in 3 studies. 12,17,25…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation